Vaccine Preventable Diseases among Mothers of Under Five Children (Indian Journal of Public Health Research & Development, 2021)
A quasi experimental study was conducted using one group pre test and post test research design. Convenientsampling technique was used to select 50 mothers of under five children at Bagavati village, of BagalkotDist, Karnataka. Data was collected using structured knowledge questionnaire.Result: The results reveal that the overall mean score was 30% in the pre test and 65.5% in the post test.Majority of the mothers had inadequate knowledge in pre test. After the implementation of InformationBooklet with an enhancement of 33.5% mothers of under five children had more adequate knowledgeregarding Vaccine Preventable Diseases. Paired ‘t’ test showed that there was a significant improvementbetween pre test and post test scores with ‘t’ value of 11.03 at P
Keywords: Knowledge; information booklet; vaccine; preventable; underfive children .